Pemanfaatan Kompor Listrik Rumah Tangga Sebagai Pengganti Penangas Air Pada Analisis Kadar Lemak Metode Soxhlet: Use Of Household Electric Stoves As Substitute For Water Baths In The Soxhlet Method Of Crude Fat Content - Sri Sulastri; Dwi Kusuma Purnamasari; Sumiati Sumiati (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
This research was conducted with the aim of comparing the results of the soxhlet method of fat content analysis with a waterbath, dan the soxhlet method of fat content analysis with a householh electric stove. Soxhlet is a method of analyzing the fat content with the principle of extracting solvent in the soxhlet flask is heated according to the boiling point so that in evaporates and extracts the fat in the sample. The collected extract is heated again so that the solvent will evaporate again and the fat will be left in the flask.Thus, recycling of the solvent occurs so that each material is extracted with a new solvent. The result of these two tools can be used to analyze fat content with ccurate results. The results showed that the levels of corn fat, moringa flour and rice bran using a water bath andhousehold electric stove were the same, namely 3,99 %, 4,65 % and 7,81 %, at the same temperature and time. Based on these results it can be concluded that household electric stoves can be used as heaters in the analysis of fat content in addition to waterbath. Besides that, household electric stoves have the advantage of being cheap and easy to obtain, compared to waterbath.